Experimental Study on the Effect of Tabs with Asymmetric Projections on the Mixing Characteristics of Subsonic Jets - S. B. Jabez Richards; S. Thanigaiarasu; M. Kaushik (Journal of Applied Fluid Mechanics, 2023)
This study experimentally explores the effect of tabs with asymmetric projections on the mixing effectiveness of jets at different nozzle exit Mach numbers with subsonic ranges of 0.4, 0.6, and 0.8. The results obtained with the tab-controlled jet are compared with those of uncontrolled jets. In this experimental investigation, a pair of identical tabs is deployed along a diameter of a convergent nozzle with inlet and exit cross sections of a circle, where each tab has two triangular projections configured at locations offset to each other at a distance of 1 mm on a plain rectangular stem. The geometrical blockage due to the presence of both tabs is maintained at 5.09% to minimize the thrust loss incurred due to tabs. The counter-rotating vortices generated at different locations of the tabs, caused instability or shear distortions at the nozzle exit, promoting jet mixing and eventually leading to rapid velocity decay along the jet axis and accentuating the reduction of the potential core. Compared to plain jet, reductions in core length of about 70%, 76%, and 81% at Mach 0.4, 0.6, and 0.8, respectively, are observed with the tab-controlled jets. The total pressure decay characteristics in the radial profile along the tab and normal-to-tab orientations have shown significant distortion in the jet structure, making it asymmetrical again owing to the asymmetrical positioning of projections on the tabs. Besides, in comparison with the plain nozzle, the total pressure decay characteristics in the radial profiles of tab-controlled jets are significantly different along the axial locations in the downstream direction due to the same reason of the asymmetrical positioning of triangular projections on the tabs. The primary research goal of this experimental investigation with asymmetrical tabs is to promote jet mixing asymmetrically to achieve thrust vectoring of jets.